PERPINDAHAN PARTAI DAN EFEKNYA TERHADAP SISTEM KEPARTAIAN - Andi Ali Armunanto (Magister Ilmu Politik Universitas Hasanuddin, 2016)
This paper is aimed to examinethe phenomenon of party switcing that conducted by politicians. Author tries to look at the various factors that could encourage politicians to make the party switching. In addition, the authors also try to see what is the long-term and short-term effects of party switching on political party and party system. Data shown in this paper is the data that derived from researchs that conducted by some researchers previously, and it is analyzed by using a different approach.